Translation Techniques and Accuracy in Rendering Mock Politeness in the Fan-Subtitled Movie Freedom Writers - Abdussalam Jabaruddin Yamjirin; Mangatur Nababan; Henry Yustanto (Anglophile Journal, 2025)
Sarcasm, as a weaponised form of politeness, poses one of the most intricate challenges in translation, its meaning concealed beneath civility, its intent barbed with social critique. This study investigates the rendering of such utterances, specifically mock politeness or off-record impoliteness, in the Indonesian fan-subtitled version of the movie Freedom Writers. Drawing on Culpeper’s impoliteness theory, the research identifies 42 instances of mock politeness and examines the translation techniques used, following Molina and Albir’s taxonomy. Translation accuracy is evaluated using Nababan et al.’s assessment framework. The findings indicate a strong reliance on Established Equivalence (65.5%) and Variation (18.3%), reflecting the translators’ preference for natural target-language expressions. Out of the 42 utterances, 40 translations (95.2%) were deemed accurate, with one less accurate and one inaccurate instance, both involving a loss of pragmatic force. These results demonstrate that most sarcastic utterances were successfully transferred across languages and cultures, though certain subtleties, particularly tone and speaker intent, remained vulnerable to distortion. The study offers fresh insight into the complexities of pragmatic translation within non-professional audiovisual contexts and underscores the importance of sensitivity to sociocultural nuance in rendering indirect impoliteness effectively. The research illustrates how fan translators navigate fidelity and naturalness in the presence of covert impoliteness and demonstrates that in non-professional settings, high accuracy is possible when there is an intuitive preservation of pragmatic intent, providing evidence for the need for pragmatic awareness in audiovisual translation.